Performance of Controlled Flow Stabilized Adobe Utilizing Construction and Demolition Waste - Ahmed, Md Imran; Renukadevi, M. V.; Joshi, Ashwin M.; Basutkar, S. M. (Civil Engineering Journal, 2026)
Due to rapid urbanization and environmental degradation from construction and demolition waste (CDW), effective management, recycling, and reuse of CDW become a necessity. CDW can be appropriately utilized in the development of alternate masonry units, such as stabilized adobe blocks (SAB). However, challenges concerning production uniformity and consistency in the characteristics of SAB exist and require further investigation. To address these issues, this study aims to develop novel controlled flow-stabilized adobe (FSAB) incorporating CDW. This research involves collecting and processing CDW as a substitute for natural soil in the development of FSAB. An experimental study investigates physical, mechanical, and durability characteristics of FSAB as per Bureau of Indian Standards. CDW-based FSAB satisfied minimum block density, water absorption, and compressive strength requirements, confirming its suitability for Class 5 soil-based blocks. Sustainability analysis indicates the embodied energy and carbon equivalent of FSAB possess significant savings, equivalent to conventional masonry units. Environmental indicators such as embodied energy per unit strength, embodied carbon per unit strength, and structural efficiency highlight the potential of CDW-based FSAB as a sustainable alternative to conventional masonry units. These findings demonstrate pathways for waste valorization and reduced dependence on conventional materials while addressing environmental and structural performance challenges.